2005
DOI: 10.1038/sj.onc.1208214
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination between serous low malignant potential and invasive epithelial ovarian tumors using molecular profiling

Abstract: Tumors of low malignant potential (LMP) represent 20% of epithelial ovarian cancers (EOCs) and are associated with a better prognosis than the invasive tumors (TOV). Defining the relationship between LMPs and TOVs remains an important goal towards understanding the molecular pathways that contribute to prognosis, as well as providing molecular markers, for these EOCs. To this end, DNA microarray analyses were performed either in a primary culture or a tumor tissue model system and selected candidate genes show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
89
1

Year Published

2005
2005
2008
2008

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 75 publications
(100 citation statements)
references
References 101 publications
10
89
1
Order By: Relevance
“…Gene expression of epithelial ovarian cancer C Le Page et al Interestingly, our LMP tumours showed the least distinct profile in comparison to NOSE (Figure 1), which correlates with the weak aggressive potential of these tumours and the favourable prognostic for the patient. The present results correlate well with recent attempts to distinguish LMP and solid malignant tumours using a microarray and gene profiling approach (Gilks et al, 2005;Meinhold-Heerlein et al, 2005;Ouellet et al, 2005). Here, we detected only a very small set of genes differentially expressed in LMP tumours.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Gene expression of epithelial ovarian cancer C Le Page et al Interestingly, our LMP tumours showed the least distinct profile in comparison to NOSE (Figure 1), which correlates with the weak aggressive potential of these tumours and the favourable prognostic for the patient. The present results correlate well with recent attempts to distinguish LMP and solid malignant tumours using a microarray and gene profiling approach (Gilks et al, 2005;Meinhold-Heerlein et al, 2005;Ouellet et al, 2005). Here, we detected only a very small set of genes differentially expressed in LMP tumours.…”
Section: Discussionsupporting
confidence: 91%
“…As previously described (Ouellet et al, 2005), RNA was linearly amplified by Alethia Biotherapeutics (Montreal, QC, Canada). The RAMP RNA produced is ( þ ) sense.…”
Section: Quantitative Pcrmentioning
confidence: 99%
See 3 more Smart Citations